2019
DOI: 10.1038/s41598-019-53333-9
|View full text |Cite
|
Sign up to set email alerts
|

A pore-occluding phenylalanine gate prevents ion slippage through plant ammonium transporters

Abstract: Throughout all kingdoms of life, highly conserved transport proteins mediate the passage of ammonium across membranes. These transporters share a high homology and a common pore structure. Whether NH3, NH4+ or NH3 + H+ is the molecularly transported substrate, still remains unclear for distinct proteins. High-resolution protein structures of several ammonium transporters suggested two conserved pore domains, an external NH4+ recruitment site and a pore-occluding twin phenylalanine gate, to take over a crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The fractional electrical distance indicated that the ammonium ion passes about 35% of the membrane electric field before the rate‐limiting binding to the protein. This is similar to other investigated plant AMT1s and might imply deprotonation by a conserved twin His motif, found in all wheat AMTs (Ganz et al 2019, 2020). Albeit, the wheat seedlings failed to downregulate the expression of the high‐affinity ammonium transporters when exposed to very high ammonium (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The fractional electrical distance indicated that the ammonium ion passes about 35% of the membrane electric field before the rate‐limiting binding to the protein. This is similar to other investigated plant AMT1s and might imply deprotonation by a conserved twin His motif, found in all wheat AMTs (Ganz et al 2019, 2020). Albeit, the wheat seedlings failed to downregulate the expression of the high‐affinity ammonium transporters when exposed to very high ammonium (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Each subunit of the homotrimer contains an external NH 4 ϩ recruitment site that attracts positive ions. This is followed by a diphenylalanine constriction region (25). In contrast to, e.g., potassium channels (26), static AMT structures do not provide evidence of a continuous water-filled pore that is wide enough to pass solutes.…”
mentioning
confidence: 86%
“…The position of the twin-His motif in the protein would be in accordance with deprotonation of the substrate after crossing about 40% of the membrane electric field (Ullmann et al 2012). As proposed for other AMT/Mep/Rh members, the deprotonation might therefore take place at the position of the twin-His motif in the transporter pore (Ganz et al 2019(Ganz et al , 2020. The first histidine residue in the twin-His motif was not essential for the deprotonation but mutation into a glutamate residue in AtAMT2 decreased the dependence on deprotonation, increased the transport rate, and allowed some bypassing of potassium and possibly ammonium ions (Ganz et al 2020).…”
Section: Discussionmentioning
confidence: 58%
“…Two conserved structures, a double Phe-gate and a twin-His motif, are lining AMT/Mep transporter pores. While the Phe-gate of AtAMT1;2 does not seem to be involved in deprotonating the ammonium substrate (Ganz et al 2019), the twin-His motif of AtAMT1;2 was shown to Fig. 1 Ammonium transport kinetics of CaMep1 ammonium transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation